Newspapers Published by Croats in New South Wales: From Print Environment to Social Networking Sites. Issue 2 (3rd April 2022) - Hebrang Grgić, Ivana
ABSTRACT: First Croatian immigrants came to Australia at the beginning of the nineteenth century, and today, they are a significant part of Australian multicultural society. Due to specific information needs, Croats of NSW began publishing newspapers in the Croatian language in the 1920s. The paper presents communication of Croatian immigrants in NSW through serial publications, on the examples of newspapers before WWII, between WWII and 1990 and after 1990. After 1990, in addition to newspapers, communication on social networking sites is analysed. Selected newspapers and presence on social networking sites show publication and editorial models, types of publishers, languages of publication and interactions with readers. The availability of publications in libraries is analysed.